ASSESSMENT OF REHABILITATION EFFECTIVENESS FROM THE PATIENT’S PERSPECTIVE BEFORE AND AFTER TOTAL HIP AND KNEE ARTHROPLASTY - Tilyakov Kh.A.; Tilyakov A.B.; Temurov A.A. (Central Asian Journal of Medicine, 2025)
Amid a rapid increase in total hip and knee arthroplasty (THA and TKA) procedures in Uzbekistan, this study aimed to identify discrepancies between patients’ expectations prior to surgery and their actual experiences postoperatively.